Effects of nightlife noise in a city center - Iannace Gino; Trematerra Amelia; Lombardi Ilaria (Noise Mapping, 2021)
The term Movida takes its name from the evening and night life of the city for their liveliness and animation. During the Movida, noise is one of the problems in the city centers due to the negative effects on the resident population. This paper reports the effects of noise due to the Movida phenomenon within the city center in southern Italy. Along the roads affected by the Movida phenomenon, the values of sound levels in dBA were measured both with fixed stations with a sound level meter and with mobile stations by wearing a noise dosimeter a participant of Movida. The measured noise levels are between 85 dBA to 90 dBA. The noise levels show that the Movida phenomenon generates disturbing conditions on the resident population with consequent conflict between club managers, patrons and residents.